Recent Developments in Modeling and Applications in Statistics - Oliveira, Paulo Eduardo (2017)
Statistics has been a main tool in almost every field of activity and an essential part of applied scientific work, supporting conclusions and offering insights into new uses for established methodologies, thus making it a valuable resource in looking for faceless facts. Model construction describing populations or phenomena subject to randomness use a wide range of methods. Data collection provides the basis for modelling and assumption verification. Modelling must be conducted using suitable techniques that give researchers the means to search for hidden facts or behaviours. This may be addressed by fitting pre-defined shapes and distributions to the data or by allowing the data to reveal its intrinsic properties by using nonparametric methods. This volume contains a selection of contributions presented at the XVIII Annual Congress of the Portuguese Statistical Society.